Headache and art: ex-voto as art of devotion and gratitude - Pereira, Moema Peisino; Andrade-Valença, Luciana Patrízia A.; Silva, Amanda Araújo da; Silva-Néto, Raimundo; Silva, Louana C.; Oliveira, Daniella Araújo de; Martins, Hugo André de Lima; Bordini, Carlos Alberto; Valença, Marcelo Moraes (Headache Medicine, 2013)
In this article the authors review the use of ex-vote as an art form expressing devotion and gratitude. Ex-voto may be manifested as objects or paintings, as a form of thanksgiving for an answered prayer or a blessing received. Several saints are invoked when one is dealing with incapacitating headaches, such as St. Denis, St. Acacius, Saint Gemma and St. Teresa of Avila. Objects of art, including sculptures or paintings, are commercially produced on the basis of these religious practices.